Dekonstruksi Locus Delicti Pasca Putusan Mahkamah Konstitusi No. 65/PUU-XXI/2023: Analisis Chilling Effect Pada Kebebasan Akademik - Komang Hanita Ayu Arisanthi Sujana; I Gede Agus Kurniawan (Fakultas Hukum Universitas Riau, 2026)
The aims of this journal for discusses the use of social media as an instrument of public diplomacy by the Indonesian government to strengthen its national image, increase global public engagement, and expand the reach of diplomatic messaging in the digital era. The transformation of diplomacy toward digital diplomacy has positioned platforms such as Instagram, X (formerly Twitter), TikTok, and YouTube as strategic spaces for communicating Indonesian values, policies, and political positions in a more interactive, rapid, and measurable manner. Using a descriptive quantitative approach supported by engagement data, trends in netizen responses, and patterns of diplomatic content distribution, this study demonstrates that social media can enhance the effectiveness of public diplomacy through three main mechanisms: (1) broader and real-time amplification of diplomatic messages, (2) increased interactivity that strengthens emotional connections between the government and global audiences, and (3) the formation of positive perceptions through visual narratives and digital storytelling. However, this study also identifies several challenges, including the risk of misinformation, limited narrative control, and gaps in digital literacy. These findings emphasize that social media is not merely a complementary tool but has become a strategic element of Indonesian public diplomacy, requiring professional, consistent, and adaptive management in response to the dynamics of the global digital environment. This article is expected to make both conceptual and practical contributions to the future development of Indonesia’s public diplomacy strategy.